Kenya : Fiscal Transparency Evaluation Update. (IMF Staff Country Reports; Country Report, 2020)
This Fiscal Transparency Evaluation (FTE) assesses the quality of fiscal reporting in Kenya against the principles set out in the Fiscal Transparency Code. Kenya has experienced a lot of structural and economic changes since 2014. One of the key objectives of this FTE is to estimate Kenya's balance sheet, and to cover as many as possible of the entities in the public sector. The coverage of Kenya's reporting of fiscal statistics has improved considerably. The report discusses that Kenya continues to perform well in the overall transparency of its fiscal forecasting and budgeting practices (Pillar II of the Code), which is based on a strong legal framework. It does so against a backdrop of significant ongoing reforms, including far-reaching fiscal devolution to counties, and the introduction of performance-based budgeting. A recent important change in the law is expected to synchronize the submission and approval of the government's spending proposals and the tax measures in the Finance Bill. The recommendations set out under each of the pillars of this report aim to address several challenges. The report also encourages the authorities to continue with the implementation of the recommendations set out in the 2014 report, on which good or satisfactory progress has been made in about half the cases.